2014
DOI: 10.1530/joe-13-0430
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of insulin-like factor 3 and its receptor expression in boar testes

Abstract: Relaxin-like factor (RLF), now mainly known as insulin-like factor 3 (INSL3), is essential for testis descent during fetal development; however, its function in the adult testis is still being elucidated. As a major step toward understanding the as-yet-unknown function of INSL3 in boars, this study aimed to develop a time-resolved fluoroimmunoassay for boar INSL3, characterize the dynamics of INSL3 expression during development, and demonstrate the expression of the INSL3 hormone-receptor system in the testis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 57 publications
1
36
1
1
Order By: Relevance
“…A significant difference between prepuberty and the onset of puberty was detected by Minagawa et al for porcine testis. During further development, a slight but not statistical decrease was observed in the boar [55]. This was not confirmed in cats, in which we observed large variability within each postpubertal group; consequently, the values of postpubertal groups did not differ from puberty or from prepuberty.…”
Section: Discussioncontrasting
confidence: 75%
“…A significant difference between prepuberty and the onset of puberty was detected by Minagawa et al for porcine testis. During further development, a slight but not statistical decrease was observed in the boar [55]. This was not confirmed in cats, in which we observed large variability within each postpubertal group; consequently, the values of postpubertal groups did not differ from puberty or from prepuberty.…”
Section: Discussioncontrasting
confidence: 75%
“…Morphometric analyses for INSL3‐ or RXFP2‐expressing cells in fertile and subfertile bulls were performed according to our previously employed method (Minagawa et al . ; Pitia et al ). Briefly, images of at least 20 different fields per animal (fertile, n = 2; subfertile, n = 2) were obtained using a BZ‐9000 microscope (Keyence, Tokyo, Japan).…”
Section: Methodsmentioning
confidence: 98%
“…Synthetic human INSL3 peptide (Phoenix Pharmaceuticals) was labeled with 4′‐(4′‐(4,6‐dichloro‐1,3,5‐triazin‐2‐ylamino)‐4‐biphenylyl)‐2,2′:6′,2″‐terpyridine‐6,6″‐diylbis (methyliminodiacetato) (DTBTA)‐europium (Eu) (Tokyo Chemical Industry, Tokyo Japan) according to Minagawa et al (). Its bioactivity was confirmed by a cell‐based bioassay as previously described (Minagawa et al .…”
Section: Methodsmentioning
confidence: 99%
“…We also showed that receptor RXFP2 is expressed in meiotic and post‐meiotic germ cells, where INSL3 neutralisation by active immunisation with INSL3 increased germ cell apoptosis and reduced sperm output and quality, suggesting that INSL3 functions as a germ cell survival/anti‐apoptotic factor in maintaining sperm production (Sagata et al., ). However, a study using conditional mutant male mice reported that INSL3 was dispensable for germ cell survival (Huang, Rivas, & Agoulnik, ), which is in stark contrast to findings in rat (Del Borgo et al., ; Kawamura et al., ), pig (Minagawa et al., ; Sagata et al., ) and fish (Assis et al., ) models.…”
Section: Introductionmentioning
confidence: 88%
“…Boars differ from other mammals in terms of testicular morphology and function, with a higher volume percentage of Leydig cells per whole testis (Peyrat, Meusy‐Dessolle, & Garnier, ) than rodents (Ewing et al., ; Mendis‐Handagama, ) and a higher level of oestrogen production (Allrich, Christenson, Ford, & Zimmerman, ; Minagawa et al., ). We previously demonstrated that boar INSL3, like rat homolog (Anand‐Ivell, Heng, Hafen, Setchell, & Ivell, ), is secreted into the circulation and interstitial compartment and then transported into the seminiferous compartments by unknown mechanisms (Minagawa et al., , ). We also showed that receptor RXFP2 is expressed in meiotic and post‐meiotic germ cells, where INSL3 neutralisation by active immunisation with INSL3 increased germ cell apoptosis and reduced sperm output and quality, suggesting that INSL3 functions as a germ cell survival/anti‐apoptotic factor in maintaining sperm production (Sagata et al., ).…”
Section: Introductionmentioning
confidence: 99%